Typhoid fever in young children in Bangladesh: clinical findings, antibiotic susceptibility pattern and immune responses. - Farhana Khanam; Md Abu Sayeed; Feroza Kaneez Choudhury; Alaullah Sheikh; Dilruba Ahmed; Doli Goswami; Md Lokman Hossain; Abdullah Brooks; Stephen B Calderwood; Richelle C Charles; Alejandro Cravioto; Edward T Ryan; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Children bear a large burden of typhoid fever caused by Salmonella enterica serotype Typhi (S. Typhi) in endemic areas. However, immune responses and clinical findings in children are not well defined. Here, we describe clinical and immunological characteristics of young children with S. Typhi bacteremia, and antimicrobial susceptibility patterns of isolated strains. METHODS:As a marker of recent infection, we have previously characterized antibody-in-lymphocyte secretion (TPTest) during acute typhoid fever in adults. We similarly assessed membrane preparation (MP) IgA responses in young children at clinical presentation, and then 7-10 days and 21-28 days later. We also assessed plasma IgA, IgG and IgM responses and T cell proliferation responses to MP at these time points. We compared responses in young children (1-5 years) with those seen in older children (6-17 years), adults (18-59 years), and age-matched healthy controls. PRINCIPAL FINDINGS:We found that, compared to age-matched controls patients in all age cohorts had significantly more MP-IgA responses in lymphocyte secretion at clinical presentation, and the values fell in all groups by late convalescence. Similarly, plasma IgA responses in patients were elevated at presentation compared to controls, with acute and convalescent IgA and IgG responses being highest in adults. T cell proliferative responses increased in all age cohorts by late convalescence. Clinical characteristics were similar in all age cohorts, although younger children were more likely to present with loss of appetite, less likely to complain of headache compared to older cohorts, and adults were more likely to have ingested antibiotics. Multi-drug resistant strains were present in approximately 15% of each age cohort, and 97% strains had resistance to nalidixic acid. CONCLUSIONS:This study demonstrates that S. Typhi bacteremia is associated with comparable clinical courses, immunologic responses in various age cohorts, including in young children, and that TPTest can be used as marker of recent typhoid fever, even in young children.